The Effect of Visitors' Income and Costs on The Number of Visitors in Southern Karawang Tourist Areas - Dedi Mulyadi; Santi Pertiwi Hari Sandi; Asep Darojatul Romli (Westscience Press, 2023)
This research aims to find out, analyze and explain income, costs and tourist visits in the South Karawang tourist area. This research was carried out using descriptive and verification methods with path analysis. The sample size for this research was 100 respondents. Based on the results of descriptive tests, it is agreed that income and costs influence tourist visits. The results of the verification test show that there is a fairly strong relationship or correlation between income and costs. The income variable has no influence on tourist visits. There is a partial effect of costs on tourist visits which is positive and significant. And there is a simultaneous influence of income and costs on tourist visits in the South Karawang tourist area of ​​64.5% while the remaining 35.5% is influenced by other variables not examined in this research.